Identifying Emergent Social Networks at a Federally Qualified Health Center‐Based Farmers' Market. Issue 3 (19th December 2013) - Alia, Kassandra A.; Freedman, Darcy A.; Brandt, Heather M.; Browne, Teri
Abstract: Identifying potential mechanisms connecting farmers' market interventions with health, economic, and community outcomes could inform strategies for addressing health disparities. The present study used social network theory to guide the in‐depth examination of naturally occurring social interactions at a farmers' market located at a federally qualified health center located in a rural, low‐income community. Trained observers recorded 61 observation logs at the market over 18 weeks. Thematic analysis revealed a range of actors and nonhuman facilitators instrumental to the farmers' market context. These actors connected with one another for communication and relationship development, economic and financial exchange, education, resource sharing, community ownership of the farmers' market, and conflict resolution. These interactions provided opportunities for social networks to develop among attendees, which may have facilitated the acquisition of social supports related to improved health, economic and community outcomes. Results provide insight into the role social networks may play in mediating the relationship between a farmers' market intervention and individual benefits. Findings also contribute to defining the typology of social networks, which may further disentangle the complex relationships between social networks and health outcomes. Future research should identify strategies for purposefully targeting social networks as a way to reduce diet‐related health disparities.